PENEGAKAN HUKUM TERHADAP PELAKU BISNIS SKINCARE YANG TIDAKMEMATUHI REGULASI BPOM DI INDONESIA - Sofia, Sofia; Gultom, Elfrida Ratnawati; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
According to the Regulation of the Head of BPOM No. 23 of 2019 concerning Cosmetic Requirements Article 2, business actors are required to ensure that cosmetics produced for domestic distribution and/or imported for distribution in the territory of Indonesia meet the technical requirements of Cosmetic Ingredients. It is not uncommon for skincare entrepreneurs to not comply with the rules and regulations of the